1985
DOI: 10.1111/j.1471-4159.1985.tb05530.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reactive Oxygen Species on Myelin Membrane Proteins

Abstract: Fresh myelin, isolated from brainstems of adult rats, was incubated in the presence of Cu2+ and H2O2. Electrophoretic analysis of the reisolated myelin membrane revealed a gradual loss of the protein moiety from the characteristic pattern and an increase in aggregated material appearing at the origin of the gel. The aggregation of proteins was time-dependent and was concomitant with the accumulation of lipid peroxidation products reactive with thiobarbituric acid. Furthermore, during the course of incubation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…In particular, the susceptibility of myelin proteins in situ in the membrane to reactive oxygen species had been reported (Konat and Wiggins, 1985). Our present results indicate that Zn 2~-GPC cholinephosphodiesterase may be one of the myelin proteins susceptible to the attack by oxidant radicals.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In particular, the susceptibility of myelin proteins in situ in the membrane to reactive oxygen species had been reported (Konat and Wiggins, 1985). Our present results indicate that Zn 2~-GPC cholinephosphodiesterase may be one of the myelin proteins susceptible to the attack by oxidant radicals.…”
Section: Discussionsupporting
confidence: 64%
“…The greater inactivation by the Cu 2+ -ascorbate system, compared with the Fe2~-ascorbate system, may be ascribed to the higher affinity of copper ions for the phosphodiesterase, suggestive of a metal-catalyzed oxidation system using copper ions (Konat and Wiggins, 1985;Chou et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that a disruption of myelin sheath integrity of peripheral nerves might be involved, because previous work demonstrated that (1) the myelin sheath is highly susceptible to degeneration caused by H 2 O 2 (Konat and Wiggins, 1985;Richter-Landsberg and Vollgraf, 1998;Laszkiewicz et al, 1999;Mronga et al, 2004;Perfeito et al, 2007), (2) the myelin sheath is disrupted and the proximal nerve stump seals off after peripheral nerve injury (Inoue et al, 2004;Devor, 2006a;Nagai et al, 2010), and (3) the dysmyelination of peripheral nerves induced by nerve injury or by delivery of bioactive lipids, such as lysophosphatidic acid, is accompanied by spontaneous action potentials in primary afferent nerves and sensitization of sensory processing, thereby contributing to neuropathic pain hypersensitivity (Devor et al, 1989;Wallace et al, 2003;Devor, 2006b;Ueda, 2008;Zhu et al, 2012). To monitor the time course of injury-induced dysmyelination of peripheral nerves in the SNI model, we first analyzed the protein levels of MPZ, the main peripheral myelin protein, in C57BL/6 mice during 21 d after SNI.…”
Section: Sni-induced Dysmyelination Of Peripheral Nerves Is Reduced Imentioning
confidence: 99%
“…Macrophage-mediated tissue damage (Halliwell and Gutteridge, 1985;Konat and Wiggins, 1985;Halliwell et aI., 1988) in the central nervous system during inflammatory responses, in demyelinating diseases, and after peripheral nerve injury, direct brain trauma, and ischemia (Graeber et aI., 1988;McGeer et aI., 1988a,b;Gendelman et aI., 1989;Haga et aI., 1989;Konno et aI., 1989;Morioka et aI., 1991;Gehrmann et aI., 1992) is accompanied by an increased production of free radicals (Chan and Fishman, 1980;Kogure et aI., 1982;Raichle, 1983), which seem also important in Alzheimer's disease (Dellacourte et aI., 1988;Zemlan et aI., 1989;Benati et aI., 1993).…”
mentioning
confidence: 99%